Livestock management and dam removal allowed the recovery of an aquatic habitat for endangered frog and fish species in Argentinian Patagonia - Arellano, Maria Luz (2017)
Placement of fencing around a stream to prevent livestock damage and water flow restoration via removal of a dam allowed riparian and aquatic vegetation recovery (76%) in less than one month. This subsequently allowed the reintroduction of a Critically Endangered frog as well as protection of an Endangered fish species.